FORMATION OF THE CONCEPT OF PROPORTIONALITY FROM THE PERSPECTIVE OF DEVELOPMENTAL EDUCATION - Miguel, Jose Carlos [UNESP] (Univ Estadual Sudoeste Bahia, 2020)
The article discusses the process of formation of the concept of proportionality by elementary school students and the pedagogical implications of its didactic exploration in the perspective of developmental teaching. It uses extensive bibliographic research, document analysis and mathematical activities of usual teaching materials, dealing with perceptions and representations about mathematical situations involving the notions of direct and inverse proportionality. The results point to the need for teachers to consider the relationships between the lived, the perceived and the conceived in teaching the notion of proportionality, exploring different mathematical situations in the context of semiotic representations of ideas from the multiplicative field.
Keywords: Mathematical Activity; Proportionality; Developmental Teaching